Development indicators for the EU's internal energy market - literature review. (24th November 2020) - Klopčič, Alenka Lena; Hojnik, Jana; Ruzzier, Mitja; Dolšak, Janez
This paper focuses on the second dimension of the EU Commission's energy strategy - development of the fully integrated European energy market and reviews prior research on market development indicators and the methods used to assess the state of energy market development as well as aims to determine the role of regulation on energy market development. A systematic literature review covers 80 topic-relevant papers. The main findings reveal that the majority of articles refer to the effects of market reforms or market liberalisation and the adaptation of energy systems to a greater penetration of renewable energy sources into existing power systems, and the energy transition to low carbon in general. There is still substantial potential to achieve an optimal, or rather a unified, model for assessment of the overall development of the energy market, since the indicators and methods of market development have not yet been universally accepted.